2009
DOI: 10.1111/j.1542-4758.2009.00393.x
|View full text |Cite
|
Sign up to set email alerts
|

Variability in calcium, phosphorus, and parathyroid hormone in patients on hemodialysis

Abstract: Calcium, phosphorus, and parathyroid hormone (PTH) levels are routinely measured in patients undergoing chronic hemodialysis. Medications, diet, and dialytic therapies are modified based upon these lab values to achieve specific goal values in the hope of improving outcomes. However, the variability of these values in patients undergoing chronic hemodialysis has only been rarely studied. We prospectively investigated the variability of these measures in 35 patients undergoing chronic hemodialysis as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…Furthermore, recent studies have shown that high dialysate calcium concentrations acutely raise BP and worsen arterial compliance during dialysis [28] . Prospective studies support that session-to-session variability in serum calcium and phosphate levels is a predictor of mortality in hemodialysis [29,30] . Thus, shifts in calcium phosphate product may be also implicated in elevated risk of mortality associated with the long interdialytic interval.…”
Section: Calcium and Phosphatementioning
confidence: 99%
“…Furthermore, recent studies have shown that high dialysate calcium concentrations acutely raise BP and worsen arterial compliance during dialysis [28] . Prospective studies support that session-to-session variability in serum calcium and phosphate levels is a predictor of mortality in hemodialysis [29,30] . Thus, shifts in calcium phosphate product may be also implicated in elevated risk of mortality associated with the long interdialytic interval.…”
Section: Calcium and Phosphatementioning
confidence: 99%
“…One such study was performed by Levitt et al who investigated 1-month session-to-session variability in 35 HD patients. They determined significant session-tosession variability in Ca, P, and iPTH (17). Sigrist et al showed that an extended interdialytic period affected Ca and P levels (18).…”
Section: Discussionmentioning
confidence: 99%
“…This variable seemed less likely to vary widely within our population, whatever the group, as corroborated by a low SD for calcaemia in our follow-up. 16 This could be explained by the fact that calcium level is a closely regulated physiological variable. 17 Regarding baseline characteristics, differences between the 'uncontrolled SHPT' group and the other groups were observed and mainly concerned age, Charlson comorbidity index, professional status and current structure for dialysis unit.…”
Section: Discussionmentioning
confidence: 99%